KLASIFIKASI TINGKAT KEPUASAN MAHASISWA TERHADAP FASILITAS PADA FTIK UNIVERSITAS DHARMAWANGSA MEDAN DENGAN ALGORITMA NAIVE BAYES - Medi Hermanto Tinambunan; Alfiansyah Hasibuan; Sri Wahyuni; Arif Sobirin Wibowo (Bisnis-Net, 2023)
ABSTRACT Facilities are a support for the implementation of a process in a business in this case the Dharmawangsa University campus, by increasing the level of student satisfaction with the facilities available, student comfort in learning will be achieved. This study used questionnaire data on 70 respondents who were students of Dharmawangsa University. Previously, the questionnaire consisted of 42 questions. After being tested for validity and reliability, 20 questions were obtained. Then from the results of the questionnaire data, a classification of student satisfaction levels will be carried out using one of the algorithms in data mining, namely Naive Bayes. The results obtained by using the rapid miner application with 50 training data and 19 data testing data, the results obtained are a classification accuracy of 73.68% with a recall value of 83.33% and a precision of 83.33%, then there are 9 attributes that have a value dissatisfaction is higher than the satisfaction score given by respondents, this can be a concern of the leadership to improve these facilities so as to increase the level of satisfaction with the facilities provided by Dharmawangsa University.Keywords: Student Satisfaction, Data Mining, Naive Bayes